Synchronous Shifts in Nutrients and Organic Carbon Responses Over the Diatom-to-Dinoflagellate Succession - Wang, Xiaolu; Jiang, Shan; Wu, Ying; Wang, Yanna (Frontiers in Marine Science, 2022)
Phytoplankton blooms, including the diatom-to-dinoflagellate succession in coastal regions, are frequently observed by researchers through incubation experiments, albeit mainly in nutrient-enrichment conditions. This study, complementary to such previous experiments, aims at the dynamics of nutrients and organic matter during the natural community shift in a nutrient-constraint condition. A nutrient-constraint incubation experiment is conducted herein to investigate nutrient dynamics during a diatom-to-dinoflagellate succession and evaluate its effects on carbon cycling. The incubation successfully induced a transition from a diatom bloom dominated by Skeletonema costatum to a dinoflagellate bloom dominated by Prorocentrum donghaiense. Results showed that the DIP limitation triggers the succession. This experiment provides an excellent opportunity to examine how senescent bloom under nutrient stress affects the amount and bioavailability of dissolved organic matter (DOM) that is produced. Under the nutrient limitation, organic carbon production was significantly influenced by nutrient availability. Particulate organic carbon (POC) production is closely related to phytoplankton growth phases, while dissolved organic carbon (DOC) is related to nutrient structure. The relative partitioning of net production to POC is higher in the dinoflagellate-dominant stage than that in the diatom-dominant stage, which is driven by quick turnover of DOM related to nutrient structure in different stages. In terms of C:Chl a ratio, it was strongly dependent on growth phases and nutrient conditions. From the signatures of chromophoric dissolved organic matter (CDOM), the bioavailability of DOM decreased during the succession. In different phases, DOM composition varied, containing more protein-like components in the degradation phase than in the growth phases. Differences of DOM composition among varying community dominance were far smaller than different growth phases during this succession. Such an observation of a diatom-to-dinoflagellate succession and the related dynamics of nutrients and organic matter benefits the prediction of organic carbon export during community shifts in ecological models.